SOCIO-ECONOMIC FACTORS BEHIND CHRISTIAN MIGRATION TO NORTH KERALA DURING THE FIRST HALF OF THE 20TH CENTURY - K M, Suresh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The first half of the 20th century witnessed a significant migration of Christian communities to North Kerala, driven by a confluence of socio-economic factors. This study explores the interplay between agrarian reforms, economic opportunities, and social structures that facilitated this migration. The availability of fertile agricultural lands in Malabar and favorable tenancy reforms offered economic stability to Christian settlers, predominantly from central Kerala. Additionally, the spread of missionary education and healthcare played a pivotal role in equipping these communities with skills and resources to adapt to their new environment. Socio-religious networks further facilitated migration by ensuring social support and communal cohesion in the resettlement process. This migration also marked a shift in the demographic and cultural landscape of North Kerala, fostering economic development while contributing to the region’s pluralistic ethos. By analyzing archival records, oral histories, and socio-economic data, this paper seeks to highlight the intricate dynamics that shaped this historical movement and its long-term implications.